2022
DOI: 10.1088/1361-6579/ac9773
|View full text |Cite
|
Sign up to set email alerts
|

Number of trials and data structure affect the number and components of muscle synergies in upper-limb reaching movements

Abstract: Objective. Due to the variability of human movements, muscle activations vary among trials and subjects. However, few studies investigated how data organization methods for addressing variability impact the extracted muscle synergies. Approach. Fifteen healthy subjects performed a large set of upper limb multi-directional point-to-point reaching movements. Then, the study extracted muscle synergies under different data settings and investigated how data structure prior to synergy extraction, namely concatenati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Selecting the appropriate criteria for identifying motor module numbers has historically been a challenge, and it is well-recognized that these somewhat arbitrary cutoffs can impact results [22]. The increased variability in motor module numbers observed with a stricter selection criterion likely stemmed from reconstructing activity in muscles that play a minor role in locomotion, as muscle activity tends to be more variable when not substantially contributing to task demands [59][60][61][62]. As a secondary analysis of motor module numbers, we assessed how well the motor modules from the reference solution could reconstruct muscle activity from the other simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Selecting the appropriate criteria for identifying motor module numbers has historically been a challenge, and it is well-recognized that these somewhat arbitrary cutoffs can impact results [22]. The increased variability in motor module numbers observed with a stricter selection criterion likely stemmed from reconstructing activity in muscles that play a minor role in locomotion, as muscle activity tends to be more variable when not substantially contributing to task demands [59][60][61][62]. As a secondary analysis of motor module numbers, we assessed how well the motor modules from the reference solution could reconstruct muscle activity from the other simulations.…”
Section: Discussionmentioning
confidence: 99%
“…When recruiting patients, detailed recordings including basic and pathological information, such as sex, age, onset time, degree of impairment, lesion location, and rehabilitation program, should be elaborated, which contribute to the explanation of the outputs and comparisons among studies. In terms of the experimental setups, one recent study [ 162 ] revealed that in order to capture sufficient variability of the task and reduce the influence of random factors, at least five repetitions and four reaching directions are required when performing the reaching tasks; it is in any case needed to find a synthesis between the clinical needs and the requirements of motion variability inherent to the muscle synergy method. As for the number and selection of muscles, there is also no standard recommendation, while some upper limb muscles have been largely used to record muscle activities ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the expressions of synergies in different motion patterns vary. Zhao et al (2022) extracted the synergies under different numbers of trials and different arrival directions in point-to-point reaching movement experiments and found that the synergies increased with the number of trials or the number of arrival directions. When the number of experiments or the number of arrival directions reached a threshold, the synergies did not change significantly.…”
Section: Motion Coordinationmentioning
confidence: 99%